Adaptation to Culture Shock in Intercultural Communication Interactions of Malaysian Students at IDIA Prenduan - Agus Saifuddin Amin; Zian Salsabila Bidaula (al-Afkar, Journal For Islamic Studies, 2024)
Cultural differences can cause culture shock to those involved in intercultural communication interactions. Students from Malaysia are one example of students who have experienced culture shock since they decided to study in Madura. This study aims to determine the forms of culture shock experienced and efforts to interact intercultural communication in the adaptation process carried out by students from Malaysia in overcoming culture shock when studying S-1 at IDIA Prenduan. This research uses a qualitative approach with the type of case research research, the data sources used are primary and secondary data sources with the number of informants as many as 5 people. Data collection techniques use interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation and conclusions. The validity of the data used is a triangulation technique. The results of this study show that differences in socio-cultural conditions and natural weather resulted in these Malaysian students experiencing diverse forms of culture shock and almost have similarities with each other. The adaptation efforts made are not much different from each other. In all forms of culture shock they experience, they choose to survive and face all existing conditions. Overall, students from Malaysia are able to adapt in a new cultural environment.